The Effect of Debt to Assets Ratio (DAR) and Cash Ratio on Net Profit Margin (NPM) in Pharmaceutical Sub-Industry Companies Listed on the Indonesia Stock Exchange for the 2021-2025 Period - Kira Agis Meilani; Ayke Nuraliati; Ayi Astuti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The study was conducted on pharmaceutical sub-industry companies listed on the Indonesia Stock Exchange for the 2021-2025 period with the aim of determining the effect of the Debt to Assets Ratio (DAR) and Cash Ratio on Net Profit Margin (NPM). This study used a quantitative approach and the type of research was descriptive and verification. This study had a population consisting of 15 companies, but only 11 companies met the criteria. Panel data regression was used in data processing with the help of Eviews12. Data analysis methods included panel data model estimation, panel data regression model selection, classical assumption testing, coefficient of determination analysis and hypothesis testing through a t-test with a significance level of 5% (0.05). The data source for this study came from secondary data. The results of this study showed that the Debt to Assets Ratio (DAR) had a significant negative effect on Net Profit Margin (NPM), with a calculated t (2.743) > t table (2.006) and a significance value (0.008) < (0.05) and a regression coefficient value of -0.217. Cash Ratio has no significant effect on Net Profit Margin (NPM), with a calculated t value (1.887) < t table (2.006) and a significance value (0.065) > (0.05) and a regression coefficient value of 0.069. The results of the determination coefficient (Adjusted R2 ) indicate that the independent variables in this study can describe the Net Profit Margin (NPM) variable by 48.757% while the rest is influenced by factors outside this study.